Metabolomic profiles of infants classified as sudden infant death syndrome: a case-control analysisResearch in context - Chad M. Aldridge; Keith L. Keene; Cornelius A. Normeshie; Josyf C. Mychaleckyj; Fern R. Hauck (EBioMedicine)
Summary: Background: Sudden Infant Death Syndrome (SIDS) is a leading cause of postneonatal mortality. The absence of specific biomarkers of SIDS diagnosis and risk leaves a significant gap in understanding SIDS pathophysiology. Metabolomics offers an avenue to better understand SIDS biology and identifying potential biomarkers. Methods: Using Metabolon Inc., global discovery panel, we analysed 828 metabolites from post-mortem serum samples of infants from the Chicago Infant Mortality Study (CIMS) and the NIH NeuroBioBank (NBB). In total, 300 infants (195 SIDS; 105 non-SIDS) across multiple race/ethnicities (70% Black, 13% White, and 16% Hispanic) were included. Metabolite associations with SIDS were performed using Welch’s t-tests, linear and logistic regression, and network-cluster analyses. Findings: We identified thirty-five significant metabolite predictors of SIDS after adjustment for age, sex, race and ethnicity, and post-mortem interval, including ornithine (OR 21.98; p-value 6.44e-7), 5-hydroxylysine (OR 19.48; p-value 6.78e-7), 1-stearoyl-2-linoleoyl-GPC (18:0/18:2) (OR 16.80; p-value 3.4e-7), ribitol (OR 8.19; p-value 4.2e-8), and arabitol/xylitol. Using Weighted Gene Co-expression Network Analysis (WGCNA), ten metabolite clusters were identified. Four exhibited significant associations with SIDS. The two most correlated clusters were enriched for metabolites in the tyrosine metabolism pathway and lipid (sphingomyelins) pathways. Interpretation: We identified metabolite biomarkers within key biological pathways and processes (e.g., nitrogen metabolism, lipid and fatty acid metabolism, stress response, nerve cell communication, hormone regulation, oxidative stress) with potential implications in SIDS pathology. Further research is needed to validate these biomarkers in additional SIDS cohorts. Funding: The Chicago Infant Mortality Study was funded by Eunice Kennedy Shriver National Institute of Child Health and Human Development and the National Institute on Deafness and Other Communication Disorders under contract number NO1-HD-3-3188, the Centers for Disease Control and Prevention and the Association of Teachers of Preventive Medicine under cooperative agreement number U50/CCU300860-06, and the Playmates in Heaven Foundation. The current analyses were funded by Eunice Kennedy Shriver National Institute of Child Health and Human Development under 5R01HD101518-04.